2019
DOI: 10.1094/pdis-05-18-0862-re
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Progress of Brown Rust and Orange Rust and Conditions Conducive for Severe Epidemic Development During the Sugarcane Crop Season in Florida

Abstract: Brown rust (caused by Puccinia melanocephala) and orange rust (caused by P. kuehnii) are two major diseases of sugarcane in Florida. To better understand the epidemiology of these two rusts, disease severity and weather variables were monitored for two seasons in cultivars CL90-4725 (susceptible to brown rust and resistant to orange rust) and CL85-1040 (susceptible to orange rust and resistant to brown rust). Brown rust was most severe during mid-May to mid-July, whereas orange rust severity peaked during two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The uredospores of P. melanocephala germinated from 20 to 32°C and at 31°C, 40% of spores germinated and stopped germinating at 33°C. The germination of P. kuehnii uredospores dropped from 65% at 29°C to 18% at 30°C and was zero at 31°C (Sanjel et al 2019).…”
Section: Spore Morphology and Biology Of Rust Pathogensmentioning
confidence: 92%
See 3 more Smart Citations
“…The uredospores of P. melanocephala germinated from 20 to 32°C and at 31°C, 40% of spores germinated and stopped germinating at 33°C. The germination of P. kuehnii uredospores dropped from 65% at 29°C to 18% at 30°C and was zero at 31°C (Sanjel et al 2019).…”
Section: Spore Morphology and Biology Of Rust Pathogensmentioning
confidence: 92%
“…Whereas triazole (metconazole) and carboxamide (fluxapyroxad) fungicides were highly effective in reducing spore germination only at higher concentrations @ 10 μg/ml. Further it was observed that P. melanocephala is highly sensitive than P. kuehnii against the same concentration of fungicides metconazole and fluxapyroxad (Chaulagain et al 2019).…”
Section: Rust Management Through Chemicalsmentioning
confidence: 98%
See 2 more Smart Citations
“…The average temperature between the inoculation and plant evaluation (30 days) was 21.5 ºC, with a minimum of 15.5 ºC and a maximum of 25.7 ºC, and according to SANJEL et al (2019) the ideal mean temperature for the development of both rusts is between 20 and 22.2 °C. Average relative humidity of air during 30 days was 80%, with accumulated precipitation of 177.6 mm.…”
mentioning
confidence: 99%